The effect of poverty and health on the Human Development Index in Central Java Province - Novia Wulandari; Lelahester Rina; Arief Sadjiarto; Tsary Aristawati; Agnesia Datu Polim; Perdinandus Saibuma; Nadia Listyaningsih; Kaliminus Balinol (University of Merdeka Malang, 2022)
The Human Development Index (HDI) is one of the data and information used by local governments to measure the achievement of human development. This study aims to analyze the effect of the influence of the headcount on poverty ratio and health as seen from the amount of life expectancy on the Human Development Index in Central Java Province. This study was completed using multiple linear regression analysis with the help of SPSS 2.0 software. The results of this study indicate headcount of poverty ratio and health have a significant effect on the human development index, which is 95.2% and other factors influence 4.8%. Headcount of poverty ratio shows a significant negative effect on the Human Development Index in Central Java Province health as seen from the amount of the life expectancy show a positive effect and insignificant effect on the Human Development Index in Central Java Province.